First‐in‐human experience of left atrial appendage occlusion with the steerable FuStar sheath. (26th March 2018) - Kleinecke, Caroline; Gomez Monterrosas, Omar; Scalone, Giancarla; Lam, Yat‐Yin; Shin, Eun‐Seok; Bellmann, Barbara; Brachmann, Johannes; Park, Jai‐Wun
Abstract : Background: Due the wide variability of left atrial appendage morphology left atrial appendage occlusion (LAAO) remains a challenging procedure. The steerable FuStar delivery sheath was designed to allow both, transseptal access and delivery of percutaneous devices. We here report the first‐in‐human experience of LAAO with the FuStar sheath. Methods: Twenty patients (76.6 ± 8.4 years; 12 (60%) males; CHA2 DS2 ‐VASc score: 5.0 ± 2) with non‐valvular fibrillation and contraindications to oral anticoagulation underwent LAAO with the LAmbre device using the FuStar steerable sheath (Lifetech Scientific Corp., Shenzhen, China) at two german centers. Results: Successful device implantation was achieved in all patients (100%). No periprocedural complications were observed. Procedure time, fluoroscopy time, contrast media, and radiation dose were 23.4 min ± 9.2, 11.9 min ± 4.1, 96.2 mL ± 45.7, and 2718.4 cG*cm 2 ± 3835.3, respectively. Conclusion: This study demonstrates the feasibility and safety of the steerable FuStar sheath for LAAO.